(untitled) (Research, Society and Development, 2022)
The objective of the study is to analyse the index of a household stock of drugs by pharmacy students from the 7th to the 9th night shift at a higher education institution in Imperatriz-MA. This is quantitative research with a descriptive method approach. A survey had the participation of 72 students. When asked about the existence of medications in their homes, 100% of the public research stated that they had medications stored at home. Regarding the storage area for medicines in their homes, students showed a preference for the bedroom. Analgesics stood out as the therapeutic class most used by students and anti-inflammatory drugs stood out in second place. When asked about the practice of self-medication, more than half said they perform this practice. The transported data show that 77.8% of the studied population discard medications in conventional garbage. It is necessary to expand programs aimed at health education as a tool to promote awareness among the population regarding the necessary skills for packaging and disposing of medicines in homes, as these issues can compromise both man and the environment.